Embracing the new age of transparency: mental health patients reading their psychotherapy notes online. (3rd September 2019) - O'Neill, Stephen; Chimowitz, Hannah; Leveille, Suzanne; Walker, Jan
Abstract: Background: Though patients' access to clinicians' visit notes may improve patient engagement and strengthen patient–clinician relationships, it is unknown whether these benefits extend to mental health settings. Aims: Examine patients' attitudes and experiences reading their psychotherapists' notes online. Methods: Using a mixed methods design, we conducted telephone interviews and an online survey of patients at an academic medical center who had opened ≥1 of their psychotherapy notes online. Eleven patients who had read ≥6 psychotherapy notes participated in semi-structured interviews, and 85 patients completed an online survey (response rate = 24%). Results: Nearly all survey respondents (94%) agreed that having open therapy notes is a good idea, and 87% wanted it to continue. More than half reported therapy notes were "very important" (≥7/10 on 0–10 scale) for feeling in control of their care, trusting their providers and taking care of themselves. Two respondents felt offended, and 7 (11%) felt judged by something they read in a note. Interview data supported survey findings. Conclusions: Our pilot findings indicate that most patients who read open therapy notes find them valuable for understanding and engaging in their mental health care, with minimal adverse effects. Larger studies with diverse patient populations are needed.